LOCATIVE ENDINGS OF THE MASCULINE AND NEUTER PRONOMINALADJECTIVALDECLENSION IN 16TH -CENTURY LITERARY SLOVENE - Jelovšek, Alenka (Slavia Centralis, 2026)
This article presents the extent of the adoption of the dative ending in the locative singular masculine and neuter forms in adjectival and pronominal declension in the works of 16th-century Slovenian Protestant writers. Special attention is given to the third-person pronoun, which differs from the others in its syntactic properties. Based on the frequency of analogical endings in the third-person pronoun and other pronouns and adjectives, an attempt is made to identify whether syntagmatic or paradigmatic agreement played a decisive role in the establishment of this change in form.
Keywords: 16th-century Slovenian literary language; adjectival-pronominal declension; paradigmatic and syntagmatic agreement